2016
DOI: 10.1186/s12904-016-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

A palliative care link nurse programme in Mulago Hospital, Uganda: an evaluation using mixed methods

Abstract: BackgroundIntegrating palliative care (PC) and empowering the health care workforce is essential to achieve universal access to PC services. In 2010, 46 % of patients in Mulago Hospital, Uganda had a life limiting illness, of whom 96 % had PC needs. The university/hospital specialist PC unit (Makerere/Mulago Palliative Care Unit –MPCU) implemented a link-nurse model to empower hospital nurses to provide generalist PC. Over two years, 27 link nurses were trained and mentored and 11 clinical protocols developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…Nine studies are from the America , seven from Europe , three from Africa and two from Asia . Most studies were obtained in a paper format and four theses . The geographical spread highlights the worldwide attention to the field of palliative care and the achievements in implemented education initiatives.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies are from the America , seven from Europe , three from Africa and two from Asia . Most studies were obtained in a paper format and four theses . The geographical spread highlights the worldwide attention to the field of palliative care and the achievements in implemented education initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…As to class attendance, three initiatives presented a mandatory attendance after volunteer enrolment , and only one initiative exhibited mandatory enrolment and attendance . The outstanding initiatives have shown optional attendance or related with recruitment numbers . None of the research initiatives reported how recruitment figures were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations